Performance Index for Types of Clinical Research Support Service Providers for Academic Research Organizations in Japan: A Cross‐Sectional Survey. Issue 2 (26th December 2020) - Ueda, Keiko; Uemura, Naoto; Matsuyama, Kotone; Nishizaki, Yuji; Tanemura, Nanae; Asano, Kento; Otsuka, Yuki; Yanagisawa, Naotake; Otsuka, Toshiaki; Yasuno, Shinji; Ueda, Rieko; Seo, Yumiko; et al.
Abstract : The purpose of this study was to conduct a factual survey to evaluate the type of clinical research support offered by service providers (supporters) in Japanese academic research organizations (AROs). From September to October 2018, we conducted an online questionnaire targeting researchers and supporters of AROs, including individuals supporting research and development (R&D) planning, as well as those involved in study management, biostatistics, coordination, data management, monitoring, and auditing. The number of responses was tabulated for each survey item. For items with written descriptions, we compiled summaries using the inductive regression method of qualitative research. Responses were obtained from 124 researchers, 258 supporters, and 40 AROs. None of the institutions responded that they had a performance index for all types of service providers, whereas 47% of institutions had an index for 1–3 types of service providers, and 40% of institutions had no index. Many institutions responded that they had a performance index for coordinators and data management, but few responded that there was a performance index for individuals engaged in R&D and study management. Furthermore, for all evaluations of AROs and researchers, the level of supporter satisfaction was low at only 20%. There was a discrepancy between the levels of researcher expectations and the actual contribution of R&D in the process of research planning. Our survey revealed that there is currently no performance index for services supporting clinical research. In future studies, we need to examine a performance index that accurately reflects the researcher attitudes revealed in this study.